PREDICTIVE MAINTENANCE: production strategy and cost reduction - Pires, Caique Aparecido; Okada, Roberto Hirochi (Revista Interface Tecnológica, 2020)
The need to ensure greater operational reliability of the equipment, cost reduction and greater availability for the production processes, made the industries look for maintenance strategies that minimized these problems. Due to its predictability of failures, predictive maintenance has become one of the best alternatives, because using information collected from the equipment, it is possible to assess which component of the machine is defective, check the severity of the failure, performing the intervention at the right time, and it is possible to plan and program all the resources needed to perform maintenance. This maintenance strategy consists of monitoring techniques that occur periodically, the collected data are stored to obtain history and compare with the most recent collections, analyzing the evolution of the symptoms of the monitored machine. The emergence of Industry 4.0 and its technologies makes predictive maintenance more efficient, assertive and economical, being one of the pillars of this new Industrial Revolution.